'Beduinella massiliensis', gen. nov., sp. nov. a new genus representing a new family in the phylum Firmicutes, and proposal of Beduinellaceae fam. nov. (November 2016) - Traore, S.I.; Azhar, E.I.; Yasir, M.; Bibi, F.; Delerce, J.; Fournier, P.-E.; Jiman-Fatani, A.A.; Lagier, J.-C.; Raoult, D.
Abstract: We report here the main characteristics of a new bacterium named ' Beduinella massiliensis ' strain Marseille-P2846 T (CSURP2846P) that was isolated from a faecal specimen of a 50-year-old Saudi Bedouin female and propose the creation of a new family ' Beduinellaceae '.